Sustainable Development, COVID-19 and Small Business in Greece: Small Is Not Beautiful - Giorgos Meramveliotakis; Manolis Manioudis (Administrative Sciences, 2021)
The aim of this article is s to show that contrary to the common parlance and to the widespread belief that treats small business as “the backbone of the economy”, in the sense of being the prime motor of wealth and prosperity, therefore the underlying logic is what is good for small business will also help government achieves overall economic policy goals, the prevailing dominant idea that formulates and drives the Greek economic policy is quite the opposite. Based on textual analysis, from Greece’s Structural Adjustment Programs, to the various assessment reports, till the latest “Development Plan for the Greek Economy”, we attempt to reveal that the prevailing idea that penetrates the abovementioned texts is that “small is not beautiful”. Specifically, after indicating a policy paradox regarding the limited financial support that Greek small businesses received or expected to receive despite their vital importance to the Greek economy, we expose the “structural impediment” idea. According to the latter the existence of a large share of small business in the Greek economy is being considered as a structural impediment for economic growth and prosperity. The implication is a policy dictum that favours a form of an evolutionary natural selection process, whereby only those establishments successful enough to grow will be able to survive, thus the vast bulk of the remaining small firms will exit the market.